ПРЕНАТАЛЬНАЯ ДИАГНОСТИКА ОРОФАЦИАЛЬНЫХ РАСЩЕЛИН В ПРЕДУПРЕЖДЕНИИ ДЕТСКОЙ ИНВАЛИДНОСТИ И СМЕРТНОСТИ - Ершова-Павлова, Алла Аркадьевна; Венчикова, Наталья Александровна; Гусина, Ася Александровна; Лазаревич, Анастасия Анатольевна; Наумчик, Ирина Всеволодовна (FORCIPE, 2022)